Proton single-event effects tolerance testing of a vision processing unit for satellite use - Badat, Sa'ad (Stellenbosch : Stellenbosch University, 2025)
Badat, S. 2025. Proton Single-Event Effects Tolerance Testing of a Vision Processing Unit for Satellite Use. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/ab66f6c1-dc89-48a2-ba4c-37f9d0e09a07